Analisis Pengaruh Penambahan Geogrid pada Stabilitas Dinding Penahan Tanah GSRW (Geoforce Segmental Retaining Wall) - Moch Wilman Abdillah; Athaya Zhafirah; Rudy Febrijanto (Institut Teknologi Garut, 2026)
The construction of the Amphitheater at POLMAN Majalengka Campus 2 employed a Geoforce Segmental Retaining Wall (GSRW) structure on a slope area with unstable subsoil conditions dominated by clay shale, which is prone to weathering and reduced shear strength. Field investigations revealed cracks at the top of the slope during construction, indicating the need for a stability evaluation of the structure. This study aims to calculate and analyze the effect of geogrid reinforcement on the safety factor, deformation, and settlement of the GSRW structure through numerical simulations using Plaxis 2D. The simulations applied a Mohr-Coulomb soil model with geogrid installed at each concrete panel layer, while seismic loads were analyzed pseudostatically using the Mononobe–Okabe method with horizontal (kh) and vertical (kv) acceleration coefficients of 0.18g and 0.036g, respectively. The analysis results showed that GSRW without geogrid had a safety factor of 1.30, which is the minimum stability threshold according to SNI 8460:2017. With geogrid reinforcement, the safety factor increased to 1.82. Maximum deformation decreased from 0.25 m to 0.14 m (a 41% reduction), and settlement decreased from 5.2 cm in 38 days to 3 cm in 64 days. This study demonstrates that geogrid reinforcement significantly improves the performance of GSRW, making it highly recommended for weak soil conditions such as clay shale.